PENGELOLAAN SUMBER DAYA MANUSIA DI BADAN KEPEGAWAIAN SUMBER DAYA MANUSIA KABUPATEN SUMENEP - Enza Resdiana; Nur Inna Alfiyah; Endang Widyastuti (UPT Publikasi Dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2020)
Management of human resources in the Human Resources Personnel Agency (BKSDM) is very important to do in an effort to address strategic issues and challenges of changes and developments in the external environment that occur, especially to improve service in the field of personnel, especially for the State Civil Apparatus (ASN) within the District Government Sumenep. The purpose of this research was to find out the management of human resources at the Sumenep Regency Human Resources Agency (BKSDM). This study uses descriptive research design with a qualitative approach. The sample or informant in this study is divided into three, first is the key informant; the key informant in this study was the Head of the Sumenep Regency Human Resources Agency (BKSDM), the second was the main informant; who became the main informant in this research are employees or the State Civil Apparatus (ASN) Sumenep Regency Human Resources Agency (BKSDM). The third is additional informants; namely society. The Sumenep Regency Human Resources Personnel Agency (BKSDM) to develop and manage its human resources is very good, where it has been shown by sending delegates from employees to attend training activities, seminars and training.